2006
DOI: 10.1145/1138041.1138045
|View full text |Cite
|
Sign up to set email alerts
|

Versatility and Unix semantics in namespace unification

Abstract: Administrators often prefer to keep related sets of files in different locations or media, as it is easier to maintain them separately. Users, however, prefer to see all files in one location for convenience. One solution that accommodates both needs is virtual namespace unification-providing a merged view of several directories without physically merging them. For example, namespace unification can merge the contents of several CD-ROM images without unpacking them, merge binary directories from different pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…Conversely, Featherstitch applications could benefit from the combination of strict ordering and nonblocking writes provided by xsyncfs. Like xsyncfs, stackable module software for file systems [10,24,31,38,39,42,43] and other extensions to file system and disk interfaces [12,27] might benefit from a patch-like mechanism that represented write-before relationships and consistency requirements agnostically.…”
Section: Related Workmentioning
confidence: 99%
“…Conversely, Featherstitch applications could benefit from the combination of strict ordering and nonblocking writes provided by xsyncfs. Like xsyncfs, stackable module software for file systems [10,24,31,38,39,42,43] and other extensions to file system and disk interfaces [12,27] might benefit from a patch-like mechanism that represented write-before relationships and consistency requirements agnostically.…”
Section: Related Workmentioning
confidence: 99%
“…3) Final Remarks: A previous study has quantified the overhead that large UnionFS stacks impose to the local file system and concluded that it scales well [13]. We used Postmark and a few micro-benchmarks to perform a similar study with NFS-UnionFS, varying the stack size up to 16 layers, and found that network latency was the dominating factor.…”
Section: ) Postmark Resultsmentioning
confidence: 91%
“…Although the current Blutopia prototype does not have the ability to coalesce adjacent layers, implementing such a feature should not pose major challenges. Besides, a previous work on UnionFS, a stackable file system for the Linux operating system, found that it is highly scalable [13]. We leverage UnionFS to implement stackable storage at the file system level, as described in Section IV.…”
Section: ) Final Remarksmentioning
confidence: 99%
See 2 more Smart Citations